The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11255-016-1398-5
|View full text |Cite
|
Sign up to set email alerts
|

How many podocyte autophagosomes are there in immunoglobulin A nephropathy and idiopathic membranous nephropathy?

Abstract: Therefore, the results of the present study indicate that autophagy participates in podocyte injury and the progression of IgAN and IMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…We found that MPO is one of the top tightly interacting proteins confirmed by the protein-protein interaction network and a significantly upregulated protein (IgA/NC ratio: 5.675); furthermore, MPO is associated with the phagosome pathway [38], which is one of the three processes enriched in the IgAN patients and found that it was lower in the nephropathy group compared to the control group [41], which is the opposite the results identified in PBMCs. This finding has obscured whether there is a connection or contrast between podocytes and PBMCs.…”
Section: Discussioncontrasting
confidence: 57%
“…We found that MPO is one of the top tightly interacting proteins confirmed by the protein-protein interaction network and a significantly upregulated protein (IgA/NC ratio: 5.675); furthermore, MPO is associated with the phagosome pathway [38], which is one of the three processes enriched in the IgAN patients and found that it was lower in the nephropathy group compared to the control group [41], which is the opposite the results identified in PBMCs. This finding has obscured whether there is a connection or contrast between podocytes and PBMCs.…”
Section: Discussioncontrasting
confidence: 57%
“…Therefore, it was concluded that type I autophagy was correlated with histopathologically more progressive disease, possibly reflecting a tendency towards poorer prognosis. We have previously reported (25) that podocytes from the renal biopsies of IgAN patients possessed more autophagosomes than healthy subjects did. In this study, we found that autophagy was reduced in podocytes exposed to IgAN-derived aIgA1-conditioned medium compared to the CON group.…”
Section: Discussionmentioning
confidence: 88%
“…In the physiological state, a basal level of autophagy is required for the removal of unfolded or misfolded proteins and for protein degradation for amino acid production, among others, so as to maintain the stability of the intracellular environment [5]. Although autophagic cell death plays an important role in disease occurrence and development [5], a moderate amount of autophagy is required for kidney development and podocyte differentiation, and an imbalance of autophagy is closely related to the occurrence of glomerular lesions, IgA nephropathy, idiopathic membranous nephropathy, and other diseases [6,7].…”
Section: Introductionmentioning
confidence: 99%